2013
DOI: 10.1103/physrevb.88.155304
|View full text |Cite
|
Sign up to set email alerts
|

Carrier dynamics in Si nanocrystals in an SiO2matrix investigated by transient light absorption

Abstract: We report on investigations of optical carrier generation in silicon nanocrystals embedded in an SiO 2 matrix. Carrier relaxation and recombination processes are monitored by means of time-resolved induced absorption, using a conventional femtosecond pump-probe setup for samples containing different average sizes of nanocrystals (d NC = 2.5-5.5 nm). The electron-hole pairs generated by the pump pulse are probed by a second pulse over a broad spectral range (E probe = 0.95-1.35 or 1.6-3.25 eV), by which informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
3
22
2
Order By: Relevance
“…2), it can be concluded that, in this range, the absorption of the former becomes lower than that of the latter. This feature is consistent with the conclusions of [45] that free carrier absorption is quite adequately described by the Drude theory, which provides a quadratic dependence of the absorption cross section on the wavelength [46]. Since the density of states increases with increasing carrier energy in the conduction band for quantum-confined nanoparticles [4], it is reasonable to assume that an increase in the energy of carriers will lead to a significant increase in their absorption with decreasing photon energy [45].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…2), it can be concluded that, in this range, the absorption of the former becomes lower than that of the latter. This feature is consistent with the conclusions of [45] that free carrier absorption is quite adequately described by the Drude theory, which provides a quadratic dependence of the absorption cross section on the wavelength [46]. Since the density of states increases with increasing carrier energy in the conduction band for quantum-confined nanoparticles [4], it is reasonable to assume that an increase in the energy of carriers will lead to a significant increase in their absorption with decreasing photon energy [45].…”
Section: Resultssupporting
confidence: 87%
“…In the case of hydrogen passivation (in H-Si/SiO x ), these states do not occur and the samples do not exhibit photoluminescence in the red region. It is known that photoluminescence results from the rapid capture of charge carriers in STE states during electron-phonon relaxation from the excited states of the silicon core (referred to as the free-electron levels in the literature) [45]. In our experiments, charge carriers were excited at fairly high-lying energy levels of the nanosilicon core and then relaxed from those levels to the conduction band bottom.…”
Section: Resultsmentioning
confidence: 67%
“…As can be seen when comparing the IA spectra taken at different times, after 500 ps the IA amplitude has decreased to almost zero -indicating the near-complete relaxation (by recombination or trapping) of free carriers, monitored by the probe pulse. Noticeable is that below ~1.6 -1.7 eV, the excited state absorption increases towards lower energies; this behavior is opposite to that of the linear absorption which grows with energy, following the classical Drude model [18].…”
Section: Induced Absorption In Si Ncsmentioning
confidence: 90%
“… Prominent emission band at ~2.95 eV (~420 nm), possibly (interface-)defect related [13,[15][16][17].  Increased cross-section of the excited state absorption in the NIR range, exceeding that of the linear band-to-band absorption [18].…”
Section: Photon Up-conversionmentioning
confidence: 98%
“…Indeed, phonon-mediated electron relaxation is a major time evolution channel competing with the MEG. The conclusion about MEG efficiency in a nanoparticle can only be made by simultaneously including MEG, phonon-mediated carrier relaxation, and, possibly, other processes, such as charge and energy transfer [4,5].…”
Section: Introductionmentioning
confidence: 99%